EPIDEMIOLOGICAL CHARACTERISTICS OF VIRAL HEPATITIS B IN THE REPUBLIC OF UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article presents a retrospective epidemiological analysis of hepatitis B cases in the Republic of Uzbekistan. The study aims to identify the long-term dynamics of morbidity, trends in incidence, regional distribution, and gender-based differences. The findings can be applied to improve preventive measures and epidemiological control of the disease.